Peningkatan Produktivitas Tanaman Hidroponik Menggunakan Tenaga Surya - Fitria Hidayanti (Fakultas Teknik - Universitas Bung Karno, 2023)
Electricity is highly essential in hydroponic agriculture. To enhance the productivity of hydroponic plants, LED grow lights are used to provide illumination during the nighttime. This electrical energy is utilized for the circulation pump of the plant's nutrients and to power the LED grow lights. To address this, the approach taken is to harness solar energy and convert it into electrical energy. This conversion of solar energy into electrical energy is known as photovoltaic, which involves the use of solar cells as the device. The hydroponic system employed in this research is the Deep Flow Technique (DFT) hydroponic system. The circulation pump operates every hour for 10 minutes, while the LED grow lights are turned on from 20:00 to 24:00. On average, the plants grow approximately 0.8 to 1.5 cm per day, and the leaves grow around 1 to 2 strands per day. The total daily electricity requirement for the circulation pump amounts to 36.4 watt-hours.